Optimization of tetracycline removal with chitosan obtained from mussel shells using RSM - Topal, Murat; Topal, E. Isil Arslan (Elsevier Science Inc, 2020)
In this study, the removal of tetracycline from aqueous solutions with chitosan obtained from mussel shells was optimized and investigated using responce surface methodology. For this aim, the central composite design was used to optimize the four variable factors (sorbent dosage (0.4-1.0g), time (20-60 min), temparature (10-30 degrees C) and initial TC concentration (50-100 mg/L)) for the removal of TC from aqueous solutions by chitosan obtained from mussel shells. According to the RSM analysis results, optimum conditions for maximum TC removal efficiency were determined as 90.5 mg/L for initial TC concentration, 35.9 min for time, 29.9 degrees C for temperature and 0.4 g for sorbent dosage. It was observed that the tetracycline was crystallized on mussel shells. According to the results of XRD after adsorption, the content of mussel shells were observed as 60% calcite, 5.6% overite, 9.4% aragonite and calcium hydroxide 25%, respectively. As a result, experiments showed that chitosan obtained from mussel shells were a good adsorbant for tetracycline removal from aqueous solutions. (C) 2020 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Mussel shells; Chitosan; Removal; RSM; Tetracycline